Soil communities are affected by CO2 belowground emissions at a natural vent in Spain. (June 2016) - Fernández-Montiel, I.; Sidrach-Cardona, R.; Gabilondo, R.; Pedescoll, A.; Scheu, S.; Bécares, E.
Abstract: Natural CO2 vents have received growing interest in the last years due to their relation to CO2 capture and storage (CCS) risk assessment studies. Despite the increasing body of knowledge, mostly focused on microbial communities, scarce information is available on how geological CO2 affects mesofauna and microfauna, and their interactions. We studied microorganisms, microfauna i.e. protists and nematodes, and mesofauna communities, i.e. collembola and mites and their relationships in a natural CO2 vent at La Sima (Spain). Four CO2 flux intensities from Control (7–19 g m −2  d −1 ) to low (40–55 g m −2  d −1 ) and high fluxes (260–1600 g m −2  d −1 ), including extreme emissions (more than 10 4  g m −2  d −1 ) were studied. We found that increasing CO2 emissions from Control to high fluxes strongly affected biota abundances and richness, cascading from microorganisms to mesofauna, and resulting in reduced and less diverse populations in each of the groups levels assayed. Nevertheless, at extreme fluxes edaphic biota biomass recovered in most of the communities, suggesting that the extreme CO2 conditions are associated with high abundances of well adapted communities, although with very low diversity. Increases in abundance of bacteria, fungi and amoebae, but not ciliates, were related to increases in mesofauna richness and nematode and mesofauna abundances. Our results help to indicate the CO2 threshold from which accidental losses from CCS operations can be detected in the long-term. Highlights: A wide range of CO2 fluxes (from 13 to 10 4  g m −2  d −1 ) was studied in a mofette. Increasing CO2 fluxes resulted in reduced abundances and less diverse communities. Changes in soil moisture were related to differences in soil biota response to CO2 . Extreme fluxes favoured higher abundances but low diversity of tolerant communities.